Total pancreatectomy with remnant stomach preservation in a patient with a history of proximal gastrectomy and interposed jejunal reconstruction with right gastroepiploic conduit preservation: a case report - Masaru Matsumura; Masahiro Kobayashi; Satoshi Okubo; Shusuke Haruta; Rikako Koyama; Hironori Uruga; Junichi Shindoh; Tsunao Imamura; Yutaka Takazawa; Masaji Hashimoto (Surgical Case Reports, 2023)
Abstract Background Pancreatic head resection following proximal gastrectomy jeopardizes the blood flow of the remnant stomach owing to right gastroepiploic conduit sacrifice, thereby necessitating total gastrectomy. However, owing to its high invasiveness, concomitant remnant total gastrectomy with pancreatectomy should be avoided as much as possible. Herein, we describe our experience of total pancreatectomy with right gastroepiploic conduit preservation in a patient with a history of proximal gastrectomy and reconstruction by jejunum interposition. Case presentation A 78-year-old woman with a history of gastric cancer was followed up at our institute for multiple intraductal papillary mucinous neoplasm, and main pancreatic duct stricture in the pancreatic head was newly detected. The cystic lesion was extended to the pancreatic body. Proximal gastrectomy and reconstruction by jejunal interposition were previously performed, and the mesenteric stalk of the interposed jejunum was approached through the retrocolic route. We planned total pancreatectomy with right gastroepiploic conduit preservation. Following adhesiolysis, the interposed jejunum and its mesentery lying in front of the pancreas were isolated. The arterial arcade from the common hepatic artery to the right gastroepiploic artery was detached from the pancreas. Furthermore, the right gastroepiploic vein was isolated from the pancreas. The pancreatic body and tail were pulled up in front of the remnant stomach, and the splenic artery and vein were resected. The pancreatic body and tail were pulled out to the right side, and the pancreatic head was divided from the pancreatic nerve plexus to the portal vein. The jejunal limb for entero-biliary anastomosis was passed through the hole behind the superior mesenteric artery and vein, and gastrointestinal anastomosis using the antecolic route and Braun anastomosis were performed. Conclusions To avoid remnant total gastrectomy, right gastroepiploic conduit preservation is an optional procedure for pancreatic head resection in patients who have undergone proximal gastrectomy with reconstruction by jejunal interposition.